Cystic Dysplasia of the Rete Testis: Case Report and Systematic Review of the Literature - Giorgia Contini; Simone Frediani; Valerio Pardi; Francesca Diomedi-Camassei; Alessandro Inserra (Frontiers Media S.A., 2022)
Cystic dysplasia of the rete testis (CDRT) is a rare cause of testicular masses in children. The pathogenesis of this malformation remains unclear. It is often associated with other genitourinary anomalies, commonly presenting as agenesis or dysplasia of the ipsilateral kidney. A case involving a 9-year-old boy with a testicular lesion and ipsilateral renal agenesis, who was diagnosed with CDRT after histological examination, is reported. In addition, a systematic review of the literature was performed to better understand this pathology to design the most appropriate treatment and follow-up strategy for patients with CDRT.